Degenerate Evolution Inequalities on Groups of Heisenberg Type (Journal of Partial Differential Equations, 2020)
In this paper the nonexistence for weak solutions of some degenerate evolution inequalities on groups of Heisenberg type is studied.
Keywords: Nonexistence; degenerate evolution inequalities; groups of Heisenberg type